2016
DOI: 10.4110/in.2016.16.4.233
|View full text |Cite
|
Sign up to set email alerts
|

Vanilloid Receptor 1 Agonists, Capsaicin and Resiniferatoxin, Enhance MHC Class I-restricted Viral Antigen Presentation in Virus-infected Dendritic Cells

Abstract: DCs, like the sensory neurons, express vanilloid receptor 1 (VR1). Here we demonstrate that the VR1 agonists, capsaicin (CP) and resiniferatoxin (RTX), enhance antiviral CTL responses by increasing MHC class I-restricted viral antigen presentation in dendritic cells (DCs). Bone marrow-derived DCs (BM-DCs) were infected with a recombinant vaccinia virus (VV) expressing OVA (VV-OVA), and then treated with CP or RTX. Both CP and RTX increased MHC class I-restricted presentation of virus-encoded endogenous OVA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…DCs derived from BM cells (BMDC) were prepared as described earlier [ 78 ] with some modifications. Briefly, BM cells from femurs and tibiae of BL/6, TLR2 KO, and MyD88 KO mice were cultured in RPMI supplemented with 2 ng/ml GM-CSF and 10 ng/ml IL-4.…”
Section: Methodsmentioning
confidence: 99%
“…DCs derived from BM cells (BMDC) were prepared as described earlier [ 78 ] with some modifications. Briefly, BM cells from femurs and tibiae of BL/6, TLR2 KO, and MyD88 KO mice were cultured in RPMI supplemented with 2 ng/ml GM-CSF and 10 ng/ml IL-4.…”
Section: Methodsmentioning
confidence: 99%
“…As can be seen in the figure above, the structure of capsaicin and RTX closely resembles each other, except that Region C is a diterpene moiety of the daphnane class (Carnevale and Rohacs, 2016). Furthermore, pharmacophore clustering and docking studies reveal a close similarity between the two compounds (Hartel et al, 2006;Athanasiou et al, 2007;Carnevale and Rohacs, 2016;Elokely et al, 2016;Lee et al, 2016). Based on previous studies, four sites represent the pharmacophore of RTX, as follows: 1) 4-hydroxy-3-methoxyphenyl, 2) C20 ester, 3) C3keto, and 4) orthophenyl groups (Huang et al, 2013).…”
Section: Antineoplastic Activity Of Natural Capsaicin Analogsmentioning
confidence: 66%
“…On the one hand, studies have shown that steroidal anti‐inflammatory drugs (such as DEX) suppress the expression of pro‐inflammatory genes by inhibition of transcription factors such as NF‐κB, AP‐1 and Signal transducer and activator of transcription 4 (Stat4) preventing the transcription of inflammatory cytokines such as IL‐1β, TNF‐α, IL‐12 and INF‐γ . With respect to RTX, it is known that it performs most of its biological functions through the TRPV1 receptor, activating and then desensitizing the TRPV1 receptor producing analgesia . However, in vitro studies have shown that RTX has a significant anti‐inflammatory effect, as it inhibits the expression of NF‐κB in ML‐1a cells stimulated with TNF‐α in a dose‐dependent manner .…”
Section: Discussionmentioning
confidence: 99%
“…A molecule with therapeutic potential for the suppression of the Th1 response during T. spiralis infection could be resiniferatoxin (RTX). RTX is a vanilloid derived from a cactuslike plant named Euphorbia resinifera , an agonist of the transient receptor potential vanilloid 1 (TRPV1), which activates and then desensitizes the TRPV1 receptor, producing analgesia . Because several studies have shown that RTX exhibits anti‐inflammatory activity in both in vitro and in vivo models, our research group recently published an investigation, where treatment with RTX in the intestinal phase of infection by T. spiralis decreased rat serum levels of pro‐inflammatory mediators such as nitric oxide (NO), prostaglandin E 2 (PGE 2 ) and tumour necrosis factor α (TNF‐α), associated with a diminished intestinal pathology and parasite burden in muscle tissue .…”
Section: Introductionmentioning
confidence: 99%